2019
DOI: 10.1080/09640568.2019.1638232
|View full text |Cite
|
Sign up to set email alerts
|

Using word clouds to present farmers’ perceptions of advisory services on pollution mitigation measures

Abstract: Advice delivery is one mechanism that can be used to encourage the uptake of water pollution mitigation measures amongst the farming community, but determining who is best placed to effectively provide advice and increase adoption creates a challenge for policy makers. Through in-depth interviews, this research investigates the perspectives of both farmers and farm advisers on the delivery of water pollution mitigation advice in three agriculturally contrasting areas of England. A novel approach using word clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Additionally, content analysis was employed to identify key words and phrases in the responses provided by participants during focus groups and interviews to describe the impacts of the pandemic on ecotourism using the "Word Cloud" technique. The word cloud is a data visualization technique involving lexical analysis or analyzing a given text (Vrain and Lovett, 2019). Constructing a word cloud consist of using different font sizes to depict the frequency in the use of words or phrases as they occur in the text being analysed (Rivadeneira et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, content analysis was employed to identify key words and phrases in the responses provided by participants during focus groups and interviews to describe the impacts of the pandemic on ecotourism using the "Word Cloud" technique. The word cloud is a data visualization technique involving lexical analysis or analyzing a given text (Vrain and Lovett, 2019). Constructing a word cloud consist of using different font sizes to depict the frequency in the use of words or phrases as they occur in the text being analysed (Rivadeneira et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…2016; Ayre et al . 2019; Vrain and Lovett 2019). These were identified by speaking with the farmers and through university staff.…”
Section: Methodsmentioning
confidence: 99%
“…We were keen to speak to a range of different types of farmers and included five mixed farmers (arable and livestock, mainly dairy), four arable farmers, and one horticultural grower in the final sample. Farm advisers were also included in the study because they are a key influencer in the use of technology on-farm (Ingram 2008;AIC 2013;Rose et al 2016;Ayre et al 2019;Vrain and Lovett 2019). These were identified by speaking with the farmers and through university staff.…”
Section: Interviewsmentioning
confidence: 99%
“…The literature review also suggested that a lack of policy consistency or land manger 'buy-in' to policy was a major reason for lack of continued farmer engagement. Sometimes the information and advice given to farmers can be contradictory even if it is coming from the same source (Vrain and Lovett, 2019;Rose et al, 2019). This is especially relevant in agricultural policy where, in relation to the CAP, continuous incremental changes have led to increased levels of uncertainty and policy fatigue (Hall, 2008).…”
Section: Negative Previous Experiences and Complex Bureaucracymentioning
confidence: 99%
“…The importance of strong trusting relationships in the delivery of effective agrienvironment schemes is well documented with farmers trusting some advisors more than others (e.g. Sutherland et al, 2013;Mills et al, 2016;Vrain and Lovett, 2019). The benefits of trust include lower transaction costs (Dwyer et al, 2007) and adherence to more sustainable social norms of land management with decreased opportunism (Inman et al, 2018).…”
Section: Trustmentioning
confidence: 99%